Penerapan Model Technological Pedagogical and Content Knowledge untuk Meningkatkan Motivasi Siswa dalam Pembelajaran Pendidikan Agama Islam - MUHAMMAD MIFTAHUDDIN; MUHAMMAD MIFTAHUDDIN (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Student learning motivation in Islamic Religious Education (PAI) learning at SMPN 1 Sukawening tends to be low due to the dominance of conventional methods and suboptimal use of technology. This study aims to analyze the effect of the implementation of the Technological Pedagogical and Content Knowledge (TPACK) model on student learning motivation in Islamic Religious Education (PAI) subjects. This research uses a quantitative approach with an experimental method and a quasi-experimental design with a Nonequivalent Control Group Design type.Data were collected through motivation questionnaires, observation, and documentation. The results showed that the implementation of TPACK obtained teacher activity of 78.67% and student activity of 76%. The average pretest of the experimental class was 93.13 and the control class was 82.00, while the average posttest increased to 97.73 and 84.07, respectively. The t-test results showed a significance value of 0.000 <0.05, which indicated a significant difference between the experimental and control classes. The increase in learning motivation in the experimental class was also demonstrated by the N-Gain value of 66.9%, categorized as medium, higher than the control class's 11.5%, categorized as low. Thus, the implementation of the TPACK model provides a better increase in learning motivation compared to conventional learning in Islamic Religious Education (PAI).